2017
DOI: 10.7759/cureus.1477
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Colorectal Cancer Screening in Pakistan

Abstract: BackgroundThe prevalence of colorectal cancer (CRC) is growing in Pakistan; however, there are no national screening programs or guidelines in place to curb its development. This study was conducted with the aim of ascertaining public awareness and attitudes regarding CRC and current screening practices. Furthermore, the study assessed perceived barriers which could impact future screening processes.MethodsA cross-sectional, questionnaire-based study was conducted among urban dwellers of Karachi, Pakistan. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 24 publications
4
37
2
Order By: Relevance
“…A low perceived risk is associated with lower preventive measures [25262728]. Barriers such as cost and inaccessibility to screening centers have been identified in the literature but were not shown to be significant in our study [8141821].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…A low perceived risk is associated with lower preventive measures [25262728]. Barriers such as cost and inaccessibility to screening centers have been identified in the literature but were not shown to be significant in our study [8141821].…”
Section: Discussionmentioning
confidence: 61%
“…This is higher than the screening rate of CRC in Saudi Arabia, which was found to be 8.6% [19], and closer to that in Spain, where 12% of the surveyed population had undergone CRC screening [20]. In fact, the lack of knowledge that one should get screened has been found to be one of the most common barriers to CRC screening [914181921]. Primary care physicians were shown to play an important role in recommending CRC screening and increasing awareness of screening guidelines [10].…”
Section: Discussionmentioning
confidence: 99%
“…Pakistan, like many other South Asian countries, have been placed in low-risk zone CRC. Though, a latest study have reported in CRC cases for patients above the age of 50 years (Hasan et al, 2017). From global perspective, Pakistan falls into a high-risk region for colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in contrast to many other countries where programs need to be paid out of pocket or where significant population subgroups may lack health insurance (for example Pakistan [ 2 ]), South Korea [ 3 ] or the US [ 4 ] there should not be financial barriers for accepting the screening offer in the Danish setting. However, despite the free offer, around 40% of Danes do not participate when they are initially invited [ 5 ].…”
Section: Introductionmentioning
confidence: 99%